2021
DOI: 10.3389/fphar.2021.786596
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and Non-alcoholic Fatty Liver Disease: An Umbrella Review and a Systematic Review and Meta-analysis

Abstract: Background: The effects of coffee consumption on hepatic outcomes are controversial. This study investigated the associations between coffee consumption and the incidence of non-alcoholic fatty liver disease (NAFLD) in the general population and the reduction of liver fibrosis among patients with NAFLD.Methods: The study consisted of two parts: an umbrella review and a systematic review and meta-analysis (SRMA). The searches for each part were performed separately using PubMed, EMBASE, Cochrane, Scopus, and CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
1
23
1
Order By: Relevance
“…NAFLD patients who drink three to four cups of coffee per day will have more health benefits than harm, with the reduction in risk for various health outcome[ 109 ]. Nevertheless, a recent meta-analysis of 11 epidemiological studies confirmed association with regular coffee consumption and decreased risk of NAFLD[ 110 ].…”
Section: Dietary Intervention Studies In Nafld Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…NAFLD patients who drink three to four cups of coffee per day will have more health benefits than harm, with the reduction in risk for various health outcome[ 109 ]. Nevertheless, a recent meta-analysis of 11 epidemiological studies confirmed association with regular coffee consumption and decreased risk of NAFLD[ 110 ].…”
Section: Dietary Intervention Studies In Nafld Patientsmentioning
confidence: 99%
“…It was noted that decaffeinated coffee has the same helpful effect on NAFLD[ 114 ]. It was considered that two cups of coffee/day helped in the prevention of hepatocellular carcinoma[ 115 ], while three cups of coffee/day prevented steatohepatitis and fibrosis[ 109 ]. As observations have so far been based on epidemiological studies, future clinical studies need to confirm whether coffee consumption can be considered a preventative factor for NAFLD.…”
Section: Dietary Intervention Studies In Nafld Patientsmentioning
confidence: 99%
“…Anty et al found that regular coffee, but not espresso, was protective against fibrosis in a group of morbidly obese European women [ 34 ]. Recent meta-analyses show a consensus that coffee intake protects against fibrosis for subjects with NAFLD [ 6 , 39 , 40 , 41 , 42 , 43 ], but there is a lack of agreement on whether coffee intake has any effect on NAFLD incidence in the general population, with three of these studies supporting an effect [ 40 , 42 , 43 ] and the other three concluding that there is no effect [ 6 , 39 , 41 ]. Our study found a significantly higher level of caffeine metabolites in subjects without fibrosis compared to those with fibrosis ( Figure 3 ), but failed to find significant correlation between coffee metabolites and fibrosis, when studied as a continuous variable ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…An umbrella review is an increasing popular approach that systematic collects and evaluates information from systematic reviews and meta-analyses, which is used to consolidate the highest level of evidence on a given topic (usually clinical associations), and inform clinical practice as well as public health policies. 8 Previously, several umbrella reviews related to NAFLD have been published to summarise the quality of evidence regarding the associations between nutritional, lifestyle, metabolic factors and NAFLD, [9][10][11] and effects of sodium glucose co-transporter 2 (SLGT2) 12 and resveratrol supplementation 13 in patients with NAFLD. However, no umbrella review was conducted for issue of the extra-hepatic morbidities and mortality of NAFLD currently.…”
Section: Introductionmentioning
confidence: 99%